STUDY OF WOMEN SELF HELP GROUP IN THE RURAL AREAS OF BIHAR - GYANESHWAR PASWAN (International Journal of Multidisciplinary Research and Studies, 2020)
In line with this many effort have been initiated towards poverty eradication using a technique of formation of people in to self-help groups (SHG). The idea of forming people in to groups is to enhance them the ability and provide opportunities to get employment through collaborative support where they can work collectively to come out of the clutches of poverty. Therefore, SHG is one of the platforms that provide opportunities to people to engage in the group to achieve a common goal. The involvement in the SHG guaranteed to get access on other financial aid and support through the SHPIs or financial institutions like banks and NGOs. It is seen that people engaging in the SHG movement can either work collaboratively for IGAs or individually taken up for any IGAs mainly in the activities of farming, animal husbandry, small scale business, handloom and handicraft, etc.